KEBIJAKAN PENDIDIKAN ISLAM DI PERGURUAN TINGGI AGAMA ISLAM SWASTA - Muhammad Zaim (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The growth of Islamic higher education institutions (PTAI) cannot be separated from the existence of private Islamic universities (PTAIS). It can be seen that the early establishment of the Islamic religious college (PTAI) actually came from a private Islamic religious college (PTAIS). In fact, the existence of a private Islamic religious university (PTAIS) existed before Indonesia's independence. In the 1930s, the desire and aspirations of Indonesian Muslims emerged to establish Islamic tertiary institutions. Admittedly or not, currently the quality of private Islamic higher education institutions (PTAIS) is still inferior to state Islamic colleges (PTAIN). This kind of image certainly does not benefit the position of the private Islamic university (PTAIS) which is in the second place. Of the number of private Islamic universities (PTAIS), there are only a few universities that are considered feasible, the rest are still below standard. The question is, what is the role of Islamic education policy in private Islamic universities (PTAIS) in improving its quality so that it can compete with state Islamic universities (PTAIN).